PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS PENDEKATAN KONTEKSTUAL PADA MATERI VEKTOR UNTUK PESERTA DIDIK KELAS X SMA/MA - Sony Horizon (Jurnal Edukasi dan Penelitian Matematika, 2021)
Videos that have a by displaying videos that contextually connect teaching material to life, learning videos with a contextual approach help media in the learning process, particularly independent learning. One of these operations is the vector material for class X SMA / MA. This research aims to create valid and practical instructional media based on video lessons and a contextual approach to vector material. This is a development research using the Plomp model, which includes a stage of preliminary research and a prototyping phase. Needs analysis, student analysis, curriculum analysis, and material analysis are also part of the preliminary research phase. The prototyping phase consists of four prototypes for creating a learning video with a contextual approach. The research found that instructional video media for class X SMA/MA with a contextual approach to vector material had a validity level of very valid category and a practicality level of very practical category. As a result, it can be concluded that learning media based on video learning with a contextual approach for class X SMA / MA students are valid and practical. Keywords — Learning Video, Contextual Approach, Vector